Antibacterial activity of different part of Neem (Azadirchta indica) growing in Sharjah, United Arab Emirates - Yaseen, Kadhim Hashim (Iraqi Journal of Science, 2022)
Aqueous and ethanolic extracts of different parts (seeds, leaves, bark) of neem plant (Azadirachta Indica) were screened for antibacterial activaties against five species of bacteria (Staphylococcus aurous, Staphylococcus epidermises, Acinetobacter baumanni, Psedommonas aeruginosa, and Escherishia coli). Different extracts 40-80 mg/L were tested using Ager-well diffusion method. Neem parts potent demonstrated for anti-bacterial activaties against all microorganisms tested. The results showed that neem seeds aqueous and ethanolic, extract have significant effects for all tested bacteria, the maximum inhibition zone by seeds cold aqueous and cold ethanolic extracts were 22 & 13 mm for E. coli and S. epidermidis respectively; while leaves extracts were given 15 & 13 mm inhabitions zones against S. aureus and E. coli respectively. But extracts were showed inhibition zone 22 & 13 mm for S. aureus and S. epidermidis respectively. The fatty acids were determine in seeds neem, the compositions resulted in detection of eight fatty acids, the maximum dominant compound is Linoleic Acid and the minimum construction is Palmiticoleic Acid, the ethanolic extracts contained, Phenol, Alkaloids, Tannins, Glycosides, while the Steroids were absent, the results gathered from this study indicated that neem plant has anti-Gram negative and Gram positive bacteria.